2020
DOI: 10.31234/osf.io/hcta4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Energizing Role for Motivation in Information-Seeking During the Early Phase of the COVID- 19 Pandemic

Abstract: Curiosity is a powerful determinant of behavior. The past decade has seen a surge of scientific research on curiosity, an endeavor recently imbibed with urgency by the WHO, which set managing information-seeking as a public health goal during pandemics. And yet, a fundamental aspect of curiosity has remained unresolved: its relationship to utility. Is curiosity a drive towards information simply for the sake of obtaining that information, or is it a rational drive towards optimal learning? We leveraged people’… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
(46 reference statements)
1
9
0
Order By: Relevance
“…Given the heterogeneity of information sources and messages, it is possible that multiple, and even incompatible mental models emerge and coexist at the individual and population levels (e.g., Alesina et al, 2020). It is likely that some of these mental models are closer to and some further away from the facts known about the pandemic (Abir et al, 2020). These processes can be viewed through the lens of the knowledge gap hypothesis in mass communication research and the related concept of the "Matthew Effect."…”
Section: Current Studymentioning
confidence: 99%
“…Given the heterogeneity of information sources and messages, it is possible that multiple, and even incompatible mental models emerge and coexist at the individual and population levels (e.g., Alesina et al, 2020). It is likely that some of these mental models are closer to and some further away from the facts known about the pandemic (Abir et al, 2020). These processes can be viewed through the lens of the knowledge gap hypothesis in mass communication research and the related concept of the "Matthew Effect."…”
Section: Current Studymentioning
confidence: 99%
“…The present results support this idea by demonstrating that individual differences in curiosity traits, that is, the general curiosity of a person, are associated with how often participants inform themselves about COVID-19-related news. Consequently, not only temporally variable curiosity states are associated with COVID-19-related information seeking (19) but also temporally stable curiosity traits. Despite the overarching influence of the pandemic on physiological and psychological well-being (20, 21), curiosity traits, as measured with the Five-Dimensional Curiosity Scale (24), remained stable over time while anxiety levels increased from before to during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Given that previous research found mixed results regarding the relationship between anxiety and information seeking, it was not clear whether curiosity alone or in addition to anxiety would be linked to real-life information seeking. Anxiety during the COVID-19 pandemic had been associated with a reduction in the willingness to wait for information (19) but also increased information-seeking behaviour (22, 23). However, anxiety was not associated with information seeking when obsessive compulsive behaviour was taken into account (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations